Pengaruh Endorsement Influencer Dan Konten Viral Terhadap Keputusan Pembelian Pada Pengguna TikTok Shop Di Depok - Rini Anggraini (CV. Denasya Smart Publisher, 2025)
The development of digital technology and social media has brought significant changes in consumer behavior, especially with the emergence of TikTok as a platform that combines entertainment and online shopping through the TikTok Shop feature. TikTok Shop allows users to make purchases directly from video content, which often involves influencer endorsements and the spread of viral content. This study aims to determine the extent to which influencer endorsements and viral content influence purchasing decisions among TikTok Shop users in Depok City. This study employs a quantitative method using purposive sampling (non-probability sampling) and data analysis through multiple linear regression. Data was collected via a questionnaire distributed to 96 respondents who are active users of TikTok Shop in the Depok area. The results indicate that influencer endorsements have a significant influence on purchasing decisions, with an R Square value of 55.6%. Meanwhile, viral content also has a significant influence, contributing 68.1%. Together, these two variables account for 74.5% of the influence on purchasing decisions. These findings demonstrate that marketing strategies involving influencers and viral content are highly effective in influencing consumer behavior on the TikTok Shop platform.